Polish Contributions to International Criminal Law - Grzebyk, Patrycja, (International Law E-books Online, Collection 2026, 2025)
The book delves into the substantial and enduring influence of Polish representatives on the development of international criminal law for decades. The authors meticulously document the crucial and distinct role played by Polish diplomats in crafting relevant international treaties and analyze the intricacies of cooperation regarding the prosecution of war criminals following both World Wars. Additionally, the book examines Polish national regulations that have impacted international law itself, alongside the jurisprudence of Polish courts concerning international crimes. Notably, some of these judgments are referenced in the works of international commissions and tribunals, demonstrating their continued relevance in contemporary discussions on immunities and the scope of responsibility for international crimes.